Equine abortion and stillbirth in California: a review of 1,774 cases received at a diagnostic laboratory, 1990–2022 - Canton, German Jose; Navarro, Mauricio; Asin, Javier; Chu, Peter; Henderson, Eileen; Mete, Asli; Uzal, Francisco (SAGE Publications, 2023)
Reproductive failure represents an important cause of economic loss for the equine industry. We reviewed the cases of equine abortion and stillbirth submitted to the California Animal Health and Food Safety Laboratory System, University of California–Davis from 1990 to 2022. A total of 1,774 cases were reviewed. A confirmed cause of abortion was determined in 29.2% of the cases. Abortion or stillbirth was attributed to infectious agents in 18.7% of the cases, with Streptococcus spp., equine herpesvirus 1, and Leptospira spp. being the most prevalent. Noninfectious causes of abortion were established in 10.5% of the cases, with umbilical cord torsion being the most common. In 70.8% of the cases, a definitive cause of abortion could not be established. Our study demonstrated the difficulties in establishing an etiologic diagnosis, even when following a standard diagnostic work-up. New diagnostic approaches are needed to improve the likelihood of reaching a final diagnosis in cases of equine abortion and stillbirth.